PENDAMPINGAN PENGEMBANGAN MUTU PENYELENGGARAAN PESANTREN PADA LEMBAGA PENJAMINAN MUTU (LPM) PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO - Maskuri Maskuri (LP2M Universitas Ibrahimy, 2019)
Abstract: Implementation of the boarding school from time to time to experience the dynamics of considerable interest to continue to be studied and explored. All schools in Indonesia continues to perform remediation efforts according to the times and the demands of society. It's time to make a breakthrough boarding innovative and creative in responding to the advancement of science and technology. As a user of the service organization of schools, the public has a